Neuromarketing and its influence on customer loyalty in a coffee production company, La Victoria 2022 - Meza-Lazo, Araceli Ivonne; Fernández-Bedoya, Víctor Hugo (LACCEI, 2023)
The objective of this research was to determine the influence of neuromarketing on customer loyalty (and its dimensions: internal marketing, communication, customer experience, incentives and privileges and information) in a coffee producing company in La Victoria, 2022, using a quantitative approach, applied type, explanatory and descriptive level, non-experimental design and transversal cut. The population consisted of the company's clients (infinite). The study sample consisted of 384 of the company's customers. The technique applied was the survey. The instrument consisted of 20 items. It was concluded that neuromarketing significantly influences customer loyalty in a coffee producing company in La Victoria, 2022 (sig.=0.000; r2=0. 5271) as well as in its internal marketing, communication, customer experience, incentives and privileges and information dimensions (sig.=0.000, r2=0.6304; sig.=0.000, r2=0.4747; sig.=0.000, r2=0.3881; sig.=0.000, r2=0.2581; sig.=0.000, r2=0.1927) respectively. Finally, conclusions and recommendations were issued.